Exact Solutions for Futures and European Futures Options on Pure Discount Bonds - Chen, Ren-Raw (Journal of Financial and Quantitative Analysis, 1992)
This paper provides closed form solutions for futures and European futures options on pure discount bonds under the Ornstein-Uhlenbeck (normal) process. A significant difference between Black's model (1976) and the model in this paper for futures options is discussed.